Philosophical foundations of information technology audit. (2015) - Rohn, Eli
The scant handful of papers that philosophically analyse auditing principles date from the 1980s. None that we know of addressed information technology audit, a rather new interdisciplinary profession. The aim of this work is to explore the basic design principles that inquiry systems supposedly must fulfil to establish valid auditing procedures. Philosophers have shown that different inquiry approaches utilise a variety of validation ('truth guarantor') mechanisms, and as such, they are also likely to lead to different outcomes. Building on Churchman's classification of inquiry systems along the lines of five Western philosophers - Leibnitz, Locke, Kant, Hegel and Singer - this article presents each philosopher's ideas and applies them to the information technology audit profession. Accordingly, future development of audit legitimacy mechanisms is recommended, and forecasts are made. Thus, understanding the theory should lead to improved practices.